Retrospective real-world pilot data on transcranial pulse stimulation in mild to severe Alzheimer's patients - Cont, Celine; Stute, Nathalie; Galli, Anastasia; Schulte, Christina; Logmin, Kazimierz; Trenado, Carlos; Wojtecki, Lars (Frontiers in Neurology, 2022)
Abstract Introduction. Transcranial Pulse Stimulation (TPS) is a non-invasive neuromodulation therapy that uses short, repetitive shockwaves. This relatively new CE-marked treatment provided first promising results in a clinical pilot study for improving cognition in mild to moderate Alzheimer’s Disease (AD). Here we present pilot real-world short-term results of TPS in mild but also moderate to severe Alzheimer´s patients from the first center in Germany. Methods. 11 patients were retrospectively examined for cognitive and emotional function before and after first stimulation series. The effect was assessed using several neuropsychological tests (Alzheimer’s Disease Assessment Scale (ADAS) including the ADAS cognitive score (ADAS Cog) and ADAS affective scores, Mini-Mental Status Examination (MMSE), and Montreal Cognitive Assessment (MoCA) as well as in comparison between the groups from mild to severe patients. Moreover, subjective improvement of symptom severity, potential effects on depressive symptoms, and side effects were analyzed using Numeric Rating Scales (NRS). Results. Side effects were rare (in 4% of sessions). Patients significantly improved in the ADAS and ADAS Cog, while there was no significant effect in MMSE and MoCA. Patients’ self-reported symptom severity significantly improved. The depressive symptoms measured in an ADAS subscale also improved significantly. Statistical data analyses indicate a better improvement in most tests of patients with severe and moderate AD compared to mild patients. Conclusion. TPS might be a safe add-on therapy for Alzheimer´s, especially for moderate to severe patients. More research on long-term effects in patients as well as studies with sham control groups is needed.